Full employment output in Ireland - Slattery, D. G. (Statistical and Social Inquiry Society of Ireland, 1978)
This paper is intended as the third in a series dealing with full employment in Ireland. The first (Slattery (1976)) was concerned with determination of a pressure of labour demand which could be regarded as consistent with full employment (of labour) and with "acceptable" rates of wage and price inflation: the second (Slattery (1977)) translated this constrained full-employment demand pressure into numbers seeking employment. Since policy measures intended to promote full employment, operate in the main by influencing aggregate supply and demand a target of full employment requires a corresponding target for output. The purpose of the present paper is to assess the output implications of full employment.
Read before the Society, 17 January 1978
Keywords: Full employment and output; Full employment in Ireland; Potential output; Policy objectives; 314.15